Functional Avidity: A Measure to Predict the Efficacy of Effector T Cells? - Selena Viganò; Daniel T. Utzschneider; Matthieu Perreau; Giuseppe Pantaleo; Dietmar Zehn; Alexandre Harari (Clinical and Developmental Immunology)
The functional avidity is determined by exposing T-cell populations in vitro to different amounts of cognate antigen. T-cells with high functional avidity respond to low antigen doses. This in vitro measure is thought to correlate well with the in vivo effector capacity of T-cells. We here present the multifaceted factors determining and influencing the functional avidity of T-cells. We outline how changes in the functional avidity can occur over the course of an infection. This process, known as avidity maturation, can occur despite the fact that T-cells express a fixed TCR. Furthermore, examples are provided illustrating the importance of generating T-cell populations that exhibit a high functional avidity when responding to an infection or tumors. Furthermore, we discuss whether criteria based on which we evaluate an effective T-cell response to acute infections can also be applied to chronic infections such as HIV. Finally, we also focus on observations that high-avidity T-cells show higher signs of exhaustion and facilitate the emergence of virus escape variants. The review summarizes our current understanding of how this may occur as well as how T-cells of different functional avidity contribute to antiviral and anti-tumor immunity. Enhancing our knowledge in this field is relevant for tumor immunotherapy and vaccines design.